The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0366-69132013000100014
|View full text |Cite
|
Sign up to set email alerts
|

Sinterização ultrarrápida por micro-ondas do compósito mulita-cordierita

Abstract: ResumoA sinterização ultrarrápida por micro-ondas é uma técnica que oferece enorme potencial para a fabricação de diversos materiais cerâmicos com microestruturas cerâmicas diferenciadas. Assim, este trabalho teve por objetivo sinterizar compósitos cerâmicos do tipo mulita-cordierita em forno de micro-ondas. Para realizar essa pesquisa, foi utilizado um compósito 60%mulita-40%cordierita, originário da empresa Scimarec Co. Amostras desse compósito foram sinterizadas em forno convencional e por sinterização ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Mullite is a refractory ceramic of great industrial importance because of its variety of applications since it can be used in traditional applications such as dishes and refractory products as well as in advanced ones, including structural and functional applications [1][2][3][4][5]. Such versatility is because of its properties, namely: low thermal conductivity, low thermal expansion coefficient, hightemperature resistance, good chemical stability, low density (3.18 g/cm 3 ), excellent creep and thermal shock resistance, high melting point, and excellent electrical resistance [1,2,[5][6][7][8][9][10]. In the Al 2 O 3 -SiO 2 phase diagram, mullite is the only stable crystalline phase up to around 1800 ºC under atmospheric pressure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mullite is a refractory ceramic of great industrial importance because of its variety of applications since it can be used in traditional applications such as dishes and refractory products as well as in advanced ones, including structural and functional applications [1][2][3][4][5]. Such versatility is because of its properties, namely: low thermal conductivity, low thermal expansion coefficient, hightemperature resistance, good chemical stability, low density (3.18 g/cm 3 ), excellent creep and thermal shock resistance, high melting point, and excellent electrical resistance [1,2,[5][6][7][8][9][10]. In the Al 2 O 3 -SiO 2 phase diagram, mullite is the only stable crystalline phase up to around 1800 ºC under atmospheric pressure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the Al 2 O 3 -SiO 2 phase diagram, mullite is the only stable crystalline phase up to around 1800 ºC under atmospheric pressure [8][9][10][11]. However, due to its high covalent bond degree, and slow diffusion of the Al 3+ and Si 4+ ions in the mullite network and grain boundaries, its production requires high temperatures, above 1600 ºC, and long sintering times to achieve good densification [2,3,6,7,9]. Atisivan et al [12] reported that mullite densification was observed at high temperatures, around 1650 ºC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation